2011
DOI: 10.4049/jimmunol.1001274
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1-Like Receptor Antagonist Attenuates Th17-Mediated Immune Response and Ovalbumin Antigen-Induced Neutrophilic Airway Inflammation

Abstract: Allergic airway inflammation is generally considered a Th2-type immune response. Recent studies, however, demonstrated that Th17-type immune responses also play important roles in this process, especially in the pathogenesis of neutrophilic airway inflammation, a hallmark of severe asthma. We previously reported that dendritic cells release dopamine to naive CD4+ T cells in Ag-specific cell–cell interaction, in turn inducing Th17 differentiation through dopamine D1-like receptor (D1-like-R). D1-like-R antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…Immune-modulation therapies, including antigen desensitization, have been applied to asthmatic patients with modest success [44]. In animal models of airway inflammation, autoimmune encephalomyelitis, nephrotoxic serum nephritis, and rheumatoid arthritis, an antagonist to the dopamine receptor has been reported to attenuate DC function and thus the immunological response [28,45-47]. Our findings extend this concept and indicate for the first time that an LABA can directly suppress the immunological response in vivo .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Immune-modulation therapies, including antigen desensitization, have been applied to asthmatic patients with modest success [44]. In animal models of airway inflammation, autoimmune encephalomyelitis, nephrotoxic serum nephritis, and rheumatoid arthritis, an antagonist to the dopamine receptor has been reported to attenuate DC function and thus the immunological response [28,45-47]. Our findings extend this concept and indicate for the first time that an LABA can directly suppress the immunological response in vivo .…”
Section: Discussionsupporting
confidence: 63%
“…Crosstalk between TLR4 and β2 ADR transduction pathways in DCs was demonstrated in vitro and in vivo [27]. Matsushita and colleagues reported that dopamine D1-like antagonists attenuate the Th17-mediated immune response through DCs and airway inflammation [28]. Therefore, we hypothesized that a β2 ADR agonist has inhibitory effects in allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…BALF samples were obtained as before [28]. Mouse lungs were flushed via the trachea cannula with 0.8 ml PBS 3 times following the final OVA challenge.…”
Section: Methodsmentioning
confidence: 99%
“…We designed a study to determine whether the D1-like-R antagonist, SCH23390, suppresses OVA-Ag-induced neutrophilic airway inflammation in OVA TCR-transgenic DO11.10 mice, and then sought to elucidate the mechanism of action [44]. Briefly, 6-week-old female DO11.10 mice were challenged with an aerosolized solution of 3% OVA or PBS for 10 min on days –2 to 0.…”
Section: Effect Of Dopamine D1-like Receptor Antagonist On Ova-inducementioning
confidence: 99%